Florida Citrus Outlook 2013/14 Season - Matthew J. Salois (EDIS)
This 24-page report provides supply, demand, and price projections of Florida citrus for the 2013/14 season based on the November 2013 forecast of the 2013/14 Florida citrus crop, by variety. Projections are for Florida orange juice and grapefruit juice pack, movement, and ending inventory, along with estimates of US consumption and retail sales of OJ and GJ, preliminary on-tree price estimates, and Brazil’s OJ outlook (given its bearing on Florida’s OJ situation). Written by Matthew J. Salois and published by the UF Department of Food and Resource Economics, September 2014.